Efficient Adaptation to Flood Risk - Winston P. Hovekamp; Katherine R. H. Wagner (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies whether private adaptation to flood risk is economically efficient. We estimate the return to elevating houses, one of the most significant private defensive investments against flooding, using two decades of microdata on the universe of houses and flood damages in high-risk flood zones in the Atlantic and Gulf Coast United States. We find that undertaking adaptation is socially optimal in the highest risk areas over a house's lifetime, but that individual homeowners may under-invest in flood protection because the benefits do not accrue over their average tenure. We identify conditions under which adaptation yields the highest returns.
Keywords: H54; Q54; Q58; 330; Überschwemmung; Katastrophenschutz; Gebäude; Effizienz; USA